Design Of Gas Leakage Monitoring System And Rfid-Based Door Security Access Control Using Blynk Application - Muhammad Salman Alfarizi (Journal Research of Social Science, Economics, and Management, 2025)
Home security and gas leak risks are critical issues requiring effective solutions. This study designs a gas leakage monitoring and door access control system based on the Internet of Things (IoT) using ESP8266, MQ-2 sensor, RFID sensor, and the Blynk application. The system detects gas levels in real-time, triggers a buzzer alert, and automatically shuts off the gas valve when thresholds are exceeded. For access control, RFID authentication is implemented to allow only registered cards. Sytem status and alerts are displayed through the Blynk app, enabling remote monitoring. Testing results show the system performs reliably and responds well to both emergency gas leaks and access authorization. This integration offers a pratical and costs-effective solution for enhancing home security and comfort.